Phospholipid headgroup-headgroup electrostatic interactions in mixed bilayers of cardiolipin with phosphatidylcholines studied by 2H NMR. - Pinheiro, T; Duralski, A; Watts, A (1994)
The headgroup-headgroup interactions in binary mixed bilayers of diacylphosphatidylcholines (PC) and cardiolipin were analyzed by 2H NMR. Specific changes in the quadrupole splittings of the choline headgroup deuterated PC at alpha,beta-methylenes, and gamma-methyls are observed upon the insertion of the negatively charged tetraacylphospholipid, cardiolipin. The effects are consistent with an electrostatic interaction between PC and cardiolipin headgroups, in which a concerted conformational reorientation of the entire phosphocholine moiety toward the membrane surface is involved. On the basis of the "choline-tilt" model by Macdonald and co-workers (1991) the variations in the quadrupole splittings are consistent with a change in orientation of the choline P-N vector up to 23 degrees for the highest cardiolipin concentrations. Additional information on headgroup conformational changes was obtained through the analysis of the dependence on temperature of the quadrupole splittings for the various deuterium-labeled segments. Evaluation of the deuterium spin-lattice (T1) relaxation times for the deuterons in the various positions of the choline headgroup in mixed bilayers of PC and cardiolipin showed that the internal fast segmental motions were not affected on addition of cardiolipin to PC membranes.